800 kV交流隔离开关的机构运动分析及平衡弹簧优化设计 - 孙玉洲; 李付永; 郭海涛; 王巧红; 夏立国; 师丽芳; 刘本学; 柴影辉 (Jixie qiangdu)
800 kV AC disconnector is one of the key equipment for extra high voltage（ EHV） substation,and the balance spring is an important component to reduce external load and improve equipment reliability.Aiming at 800 kV EHV disconnector,the mechanism kinematic analysis of main knife mechanism is completed based on the motion diagram,and the theoretical equation of the structural potential energy for disconnector is obtained.Then,the dynamic simulation analysis model of disconnector is established in ADAMS through virtual prototype technology.The difference between the elastic potential energy of the balance spring and the potential energy of the mechanism under the initial design condition is simulated.In order to further narrow the gap between the spring energy and the gravitational potential energy,this paper optimizes the spring system design.The simulation results show that the max-gap change between the optimal balance spring potential energy and the mechanism potential energy is reduced by about 28% than that of the initial.When the disconnector works,the external load required is greatly reduced.